Mapping Risk of Changes in Rainfall Pattern And Mitigation Strategies Rice Production Using Spatial Data in East Java, Indonesia - Yusmiaty Sabang; Rizka Muizzu Aprilia; Amirusholihin Amirusholihin; Permadi Setyonagoro; Ratna Dewi Judhaswati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Climate change is a global challenge that has a significant impact on the sustainability of agricultural systems and global food security. Rice productivity in East Java Province in 2024 experienced a decline of 4.78% due to prolonged drought/El Nino and climate anomalies as the main causes of production decline in several districts due to shifts in planting times (planting seasons) and crop failures. Unpredictable climate fluctuations can reduce land productivity, shorten the planting period, and threaten food price stability at the consumer level. The objective of this study was to identify the risk mapping of changes in rainfall patterns and mitigation strategies for rice productivity in East Java. The results show that, overall, rainfall in various regions in East Java does not have a significant effect (P > 0.05) on rice productivity, while spatial data-based mitigation results show that the overlay map of drought and flood risks is in the districts of Jember, Tuban, Lamongan, Bojonegoro, and Ngawi, with medium to high drought risk categories and high flood risk categories. For landslide risk zones, it was found that parts of Jember were included in the relatively high landslide risk category.